Impact of COVID‐19 on psychological distress among SME owners in Ghana: Partial least square–structural equation modeling (PLS‐SEM) approach. Issue 3 (29th September 2021) - Uzir, Md U. H.; Bukari, Zakari; Jerin, Ishraq; Hasan, Najmul; Abdul Hamid, Abu B.; Thurasamy Ramayah,
Abstract: A critical part of the national economy is small and medium enterprises (SMEs). SME owners are vital contributors to the overall economy. Due to their limited capital and assets, they are more vulnerable. In comparison to their contribution, the value of assessing SME owner's depression, anxiety, and mental stress has been very minimal during the COVID‐19 outbreak. Firms were forced to close due to lockdown, and they faced substantial business losses. Thus, this study aims to investigate SME owners' psychological distress due to business losses during this pandemic. The study used psychological parameters: Depression, Anxiety, Stress Scale‐21 (DASS‐21) to examine SME owners' psychological distress. A total number of 217 owners were surveyed through a judgmental sampling technique using a structured questionnaire. Data were analyzed employing partial least square‐based structural equation modeling (PLS‐SEM). The findings showed that DASS‐21 parameters and fear of business loss affected psychological distress. Besides, fear of business loss increases psychological distress, whereas government support lessens the distress. Theoretically, this study extended the scope of DASS‐21 scale and contributed to the literature of psychology. In terms of policy implications, this study provides useful information for government, policymakers, and SME owners about the effects mentioned above.